1979
DOI: 10.1042/bj1840697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucose on the cytosolic ration of reduced/oxidized nicotinamide-adenine dinucleotide phosphate in rat islets of Langerhans

Abstract: The maximal extractable activity of 'malic' enzyme (EC 1.1.1.40) in rat islets of Langerhans was similar to that reported for liver. Thus 'malic' enzyme may catalyse a near-equilibrium reaction in the cytosol of islets of Langerhans. Measurements of islet content of malate and pyruvate, the metabolite substrate and product of 'malic' enzyme, were therefore used to calculate the cytosolic ratio of [NADPH]/[NADP+]. This ratio was higher in islets incubated with 20mM-glucose than in islets incubated with 2mM-gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 23 publications
(14 reference statements)
4
25
0
Order By: Relevance
“…Both ratios rose in parallel in the presence of glucose. Glucose also raised the cytosolic NADPH/NADP + ratio [32,33]. These findings allow conclusions to be drawn from the whole-islet NADPH/ NADP + ratio about the mitochondrial and the cytosolic NADPH/NADP + ratios.…”
Section: Discussionmentioning
confidence: 71%
“…Both ratios rose in parallel in the presence of glucose. Glucose also raised the cytosolic NADPH/NADP + ratio [32,33]. These findings allow conclusions to be drawn from the whole-islet NADPH/ NADP + ratio about the mitochondrial and the cytosolic NADPH/NADP + ratios.…”
Section: Discussionmentioning
confidence: 71%
“…Because the pentose-P pathway is slow in beta cells, it would be left to malic enzyme and isocitrate dehydrogenase to generate NADPH. The mitochondrial energy-dependent NADP reductase, which transfers hydrogen from NADH to NADP, is not in equilibrium with the cytosolic NAD(P)/NAD(P)H system because of absolute permeability barriers for pyridine nucleotides (23,24). It is striking that pyruvate in SUR1 Ϫ/Ϫ islets is more effectively labeled than in the controls when glucose is at low levels of 5 mM, consistent with a higher rate of 13 CO 2 production and strongly suggests pyruvate cycling in SUR1 Ϫ/Ϫ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have strongly suggested that NADPH production via the malate-aspartate shuttle [162,163,164], also called pyruvate cycling [165], might be an important metabolic signal. Indeed, metabolisable insulin secretagogues increase the NADPH/NADP + ratio in rodent islets [166,167] and inhibition of NADPH formation reduces glucose-stimulated insulin secretion from rat islets [168,169]. Recent evidence suggests the existence of membrane associated aldehyde oxidoreductase-like enzyme activity in rat islets [170] and, as mentioned above, a number of oxidoreductase-like Kvβ subunits (Kvβ1, 2 and 3) are expressed in human and rat islets and INS-1 insulinoma cells [93].…”
Section: Regulation Of Kv Channel Activity In Beta Cellsmentioning
confidence: 99%